989. NICOTIANA WALPA: Solanaceae. (14th August 2021) - Chase, Mark W.; Dodsworth, Steven; Christenhusz, Maarten J. M.
Summary: The Australian species Nicotiana walpa is newly described here from plants collected at the Uluru‐Kata Tjuta National Park in the Northern Territory, Australia, and illustrated from plants cultivated at the Royal Botanic Gardens, Kew. Its discovery, ecology, cytology and cultivation are discussed.